Intellectual property rights and United States international trade laws - Herrington, Wayne W. (Oceana Pub. Dobbs FerryUS, 2002)
Covers investigations by the United States International Trade Commission under Section 337 of the Tariff Act of 1930 and United States customs service protection against imports that infringe intellectual property rights. Looks at proceedings before the United States Trade Representative concerning violations by foreign nations of international agreements or standards respecting intellectual property.